Inside Back Cover: Distinct Spatial Relationship of the Interleukin‐9 Receptor with Interleukin‐2 Receptor and Major Histocompatibility Complex Glycoproteins in Human T Lymphoma Cells (ChemPhysChem 18/2014). Issue 18 (15th December 2014) - Nizsalóczki, Enikő; Csomós, István; Nagy, Péter; Fazekas, Zsolt; Goldman, Carolyn K.; Waldmann, Thomas A.; Damjanovich, Sándor; Vámosi, György; Mátyus, László; Bodnár, Andrea
<x xml:space="preserve">Abstract</x> The bipartite spatial relationship of interleukin‐9 receptor (IL‐9R) with IL‐2R and membrane areas containing the major histocompatibility complex is revealed by using confocal microscopy, as described by L. Mátyus et al. on p. 3969. This relationship may affect the signaling capacity of IL‐9R in human T cells.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>